Mapping resilience : the influence of race, class and gender : a thesis presented in partial fulfilment for the degree of Master of Education (Adult Education) at Massey University - Lee, Geoffrey Allan (Massey University, 2002)
This study focuses on the interpretations of resilience by a number of adult learners in a bilingual teaching programme. The adult learners were enrolled in a College of Education programme and were in their second or third year of training. The relationship of resilience with race, class and gender was explored. The theoretical tradition of resilience is rooted in research that examines the way that children and adolescents survive in the face of sometimes, severe adversity. Resilience is infrequently used to describe the way that adults cope with challenging or unexpected life events. Less well explored, is the way in which adults themselves interpret resilience processes and consequently negotiate risks and have good outcomes. This inquiry, designed as a qualitative case study of six participants in a bilingual teaching class and informed by a social constructivist/critical theory perspective, was guided by the following research question: How do race, class and gender impact upon the individual's resiliency? The case study records include in-depth interviews, documentation records and informal conversation. The study found that a number of factors impacted upon the individuals' resiliency. However, these factors could be said to be present among all of the population. Individual differences are just as likely to be present in the study of resilience as in any other sociological study. Specific factors included the impact of whānau, the strength the case study participants drew from their children, the assertiveness developed from 'classism' seen to be present within New Zealand society, the finding of one's heritage, the development of Kōhanga and the need to provide a service for others. How society uses power (power over, or power with) was seen as an important societal factor in the development of resilience.
Keywords: Resilience (Personality trait); Bilingual education